Parallel scheme for real-time detection of photosensitive seizures - Alzubaidi, Mohammad A.; Otoom, Mwaffaq; Al-Tamimi, Abdel-Karim (Computers in biology and medicine, 2016)
The production and distribution of videos and animations on gaming and self-authoring websites are booming. However, given this rise in self-authoring, there is increased concern for the health and safety of people who suffer from a neurological disorder called photosensitivity or photosensitive epilepsy. These people can suffer seizures from viewing video with hazardous content. This paper presents a spatiotemporal pattern detection algorithm that can detect hazardous content in streaming video in real time. A tool is developed for producing test videos with hazardous content, and then those test videos are used to evaluate the proposed algorithm, as well as an existing post-processing tool that is currently being used for detecting such patterns. To perform the detection in real time, the proposed algorithm was implemented on a dual core processor, using a pipelined/parallel software architecture. Results indicate that the proposed method provides better detection performance, allowing for the masking of seizure inducing patterns in real time. •Healthy viewing.•Real-time detection of hazardous video content for photosensitive seizures.•Multicore parallel computation.•Seizure pattern inducer testing benchmark.